PROTOTYPE BUKA TUTUP PINTU GUDANG OTOMATIS MENGGUNAKAN SENSOR PIR BERBASIS ARDUINO NANO: PROTOTYPE BUKA TUTUP PINTU GUDANG OTOMATIS MENGGUNAKAN SENSOR PIR BERBASIS ARDUINO NANO - Sururi Sururi (LPPM Politeknik Pajajaran ICB Bandung, 2025)
This study presents the development of an automatic warehouse door prototype controlled by an Arduino Nano microcontroller using a Passive Infrared (PIR) sensor and an SG90 servo motor. The system is designed to improve operational efficiency and simplify access control in warehouse environments. Human motion detected by the PIR sensor is processed by the Arduino Nano, which subsequently controls the servo motor to open or close the door. The servo motor operates at an angle of 0° for the closed position and 180° for the open position. System testing was conducted by observing sensor responses at distances ranging from 1 to 3 meters. The results indicate that the PIR sensor detects motion accurately within the tested range, and the servo motor responds appropriately to control commands. Overall, the prototype demonstrates stable and responsive performance, making it suitable as a basic warehouse door automation solution.